“I Think Friendship Over This Lockdown Like Saved My Life”—Student Experiences of Maintaining Friendships During COVID-19 Lockdown: An Interpretative Phenomenological Study - Maloy, Amy; Main, Annischa; Murphy, Claire; Coleman, Lauren; Dodd, Robson; Lynch, Jessica; Larkin, Donna; Flowers, Paul (Frontiers in Psychology, 2022)
Covid-19 lockdown presented a novel opportunity to study the experiences of people attempting to maintain friendships in the context of worldwide, government enforced physical distancing and lockdown. Here we report on an experiential, idiographic qualitative project with a purposive sample of Scottish students. Data was collected via one-to-one on-line interviews with nine student participants (N=9). Data was transcribed and analysed using Interpretative Phenomenological Analysis (IPA)(Smith et al., 2021). Analysis highlighted three group-level experiential themes (GETs) and associated subthemes. Participants’ shared experiences of maintaining friendships were reflected in a dynamic process by which (1) ‘changes to communication’ were associated with experiences of (2) ‘effort and balance’ across friendships. Participants reported becoming particularly aware of the psychological processes involved in maintaining friendships, in turn, this was associated with (3) ‘reflection and growth.’ These experiential findings resonate well with several longstanding classic theories; however, they also speak to the particularities of the context in which the study was conducted. They suggest the need for a pandemic psychology that moves beyond the typical focus on the direct impacts of infectious disease to address the wider psychosocial impacts with equal vigour.